Developing Microteaching Competence through Project-Based Learning for Primary Teacher Education Students - Taufikin Taufikin (Ludi Litterarri, 2025)
Microteaching is a crucial preparatory stage in teacher education designed to strengthen pre-service teachers’ fundamental instructional skills prior to full classroom practice. However, traditional microteaching practices often emphasize temporary performance rather than sustained professional learning. This study examines the effectiveness of Project-Based Learning (PjBL) in improving microteaching competence among Primary Teacher Education students through a systematic review of empirical findings published between 2017 and 2025. The results demonstrate that embedding PjBL transforms microteaching into an authentic instructional design process through cycles of lesson project development, implementation, reflection, and revision. PjBL effectively enhances core teaching competencies including instructional communication, lesson sequencing, media utilization, classroom management, and student engagement. Furthermore, it strengthens professional dispositions such as confidence, reflective thinking, digital literacy, collaboration, and pedagogical creativity—competencies required for the 21st-century teaching profession. Therefore, PjBL not only improves microteaching performance but also fosters long-term classroom readiness through integrated project experiences, peer collaboration, and technology-enhanced pedagogy. These findings highlight PjBL as a transformative pedagogical model for teacher education programs that aspire to develop competent, adaptive, and future-ready primary school teachers